Features first translation confucian text “Lunyu” on russian language - D. V. Tsvetkov (Библиосфера)
This paper is about research of the manuscript “Book Sishu or Shang Lunyu, of Chinese confucianistic law. Translated by Jacob Volkov”. This manuscript is a first Russian translation of confucianistic “Analects”, made in the XVIIIth century. Reason of research was in learning of specifics of this translation. This research is based on comparative analyse of Volkovs translation with original version of “Analects”, compiled by Zhu Xi. It was explain, that there a lot of differences between Volkovs translation and original variant of “Analects”. There is a large possibility that J. Volkov translated “Analects” from unknown and, perhaps, lost version of this text.